SOSIALISASI DALAM PENGENALAN LINGKUNGAN PESISIR DAN LAUT (PENA LAUT) - Ferliana Widyasari; Yusuf Yusuf; Masrul Jaya; Wiwit Handayani; Fajar Adi; Jaquolina Kusaly; Mohammad Sayuti (Politeknik Kelautan dan Perikanan Sorong, 2022)
Indonesia's coastal and marine areas have the highest biodiversity. In recent times, the quality of the coast and the sea has begun to decline due to natural activities and human activities (exploitation of natural resources and environmental pollution). Efforts to establish an environmentally sound school is a concrete solution to address conservation problems so far, namely changing the paradigm by growing awareness of love for the coastal and marine environment from an early age and is expected to have a positive impact on the environmental conservation paradigm in the future. The purpose of this activity is to provide understanding and knowledge about the coastal and marine environment to elementary school, junior high school, high school, from this activity it is expected to create a sense of care and love for the coast and the sea. is the delivery of material in an effective, communicative and fun way interspersed with games by the resource persons, besides that, to measure the level of success of this activity, pre-test and post-test were given to participants, then from the results/values ​​of pre and post-test a pired T-test was carried out. Based on the results of the pre-test and post-test assessments, it can be concluded that there was a significant change in the students' scores, namely an increase in knowledge after getting the introduction to the coastal and marine environment